Czech Swap Curve, Economic Fundamentals and Financial Markets - Pohl, Martin; Málek, Jiří, 1953-; Kodera, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
We focus on Czech swap market in a broader context of economic and financial development and we provide extensive empirical evidence that swaps have many features of a "risk-free" asset. They are traded with sufficient liquidity and low transaction costs that make them attractive for investors. Swap curve dynamics may be decomposed into level, slope and curvature parameters known from bond markets.Level and slope parameter may be interpreted by Taylor rule like functions in terms of output gap and inflation. Level reflects mainly inflation expectations and its sensitivity to output gap is small. Slope parameter is highly sensitive to business cycle fluctuations and inflation deviation from CNB's target. Domestic monetary policy remains an important determinant of swap curve parameters with gradual market reaction. Czech swap rates are closely connected to Euro swap rates. We found level factors to be cointegrated and also slope and curvature exhibit strong sensitivity to Euro rates. Financial variables don't seem to have large impact on swap rates with the exemption of global equity markets, where we found positive correlation between level and SP500 returns. In contrast, Czech government bonds have many features historically connected to corporate bonds such as positive correlation with risky assets and business cycle fluctuations. Government bonds also showed large volatility and rising risk premia in the 2008/2009 financial crisis. Finally, we estimated forward premium and we found large and rising premium and limited support for expectation theory.
Vedoucí práce: Jiří Málek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations